HvGBSSI mutation at the splicing receptor site affected RNA splicing and decreased amylose content in barley - Feng, Xiuqin; Rahman, Md. Mostafijur; Hu, Qian; Wang, Bang; Karim, Hassan; Guzmán, Carlos; Harwood, Wendy; Xu, Qiang; Zhang, Yazhou; Tang, Huaping; Jiang, Yunfeng; Qi, Pengfei; et al. (Frontiers in Plant Science, 2022)
Granule-bound starch synthase I (HvGBSSI) is encoded by the barley waxy (Wx-1) gene and is the sole enzyme in the synthesis of amylose. Here, a Wx-1 mutant was identified from an ethyl methane sulfonate (EMS)-mutagenized barley population. There were two single-base mutations G1086A and A2424G in Wx-1 in the mutant (M2-1105). The G1086A mutation is located at the 3′ splicing receptor (AG) site of the fourth intron, resulting in an abnormal RNA splicing. The A2424G mutation was a synonymous mutation in the ninth intron. The pre-mRNA of Wx-1 was incorrectly spliced and transcribed into two abnormal transcripts. The type I transcript had a 6 bp deletion in the 5′ of fifth exon, leading to a translated HvGBSSI protein lacking two amino acids with a decreased starch-binding capacity. In the type II transcript, the fourth intron was incorrectly cleaved and retained, resulting in the premature termination of the barley Wx-1 gene. The mutations in the Wx-1 decreased the enzymatic activity of the HvGBSSI enzyme and resulted in a decreased level in amylose content and a changed morphology of starch granules. This work sheds light on a new Wx-1 gene inaction mechanism.